Peran Kiai dalam Membangun Solidaritas dan Harmoni Alumni melalui Pendekatan Halaqah di Pondok Pesantren: Perspektif Kharisma dan Otoritas Tradisional - Putri Hamidah; Muh Hanif (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study examines the role of kiai in fostering alumni solidarity through the halaqah forum at API Tegalrejo Islamic Boarding School using Max Weber’s concepts of charismatic and traditional authority. The research is motivated by the challenges of modernization, globalization, and digital technology, which may weaken social ties among pesantren alumni. Employing a qualitative approach with an instrumental case study design, data were collected through in-depth interviews, participant observation during halaqah, haul, and harlah activities, as well as documentation analysis. The findings reveal that the kiai’s charisma plays a central role in maintaining alumni loyalty, respect, and emotional attachment to the pesantren. The halaqah forum functions not only as a medium for strengthening friendship and transmitting pesantren values but also as a social space that reinforces social capital, collective solidarity, and alumni networks. The institutionalization of halaqah is supported by the continuity of the haul tradition, the kiai’s moral authority, and alumni’s strong sense of belonging to their alma mater. This solidarity has developed into collective actions in educational, social, economic, and religious fields. Furthermore, digital media contribute to sustaining alumni communication and participation, enabling the preservation of pesantren identity and values amid contemporary social change.